The construction of the curricular design of the University Professor of Biology at the National University of Misiones and the formative pathway of Education for Health and the Environment - Morawicki, Patricia Mariela (2021)
Fil: Morawicki, Patricia Mariela. Universidad Nacional de Misiones. Facultad de Ciencias Exactas, Químicas y Naturales. Departamento de Formación docente y Educación Científica; Argentina.